2014
DOI: 10.5657/kfas.2014.0751
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of Ethanol Extract of Undaria pinnatifida Root in RAW 264.7 Cells

Abstract: The anti-inflammatory effects of the ethanol extract of Undaria pinnatifida root (UPREE) were investigated using the lipopolysaccharide (LPS)-induced inflammatory response in RAW 264.7 cells by measuring the production of nitric oxide (NO), interleukin (IL)-6, tumor necrosis factor (TNF)-α, and IL-1β, and cell proliferation. We found that NO levels were reduced by 34% at 100 μg/mL. Moreover, the production of IL-6 and TNF-α was suppressed by the UPREE treatment. In particular, the IL-6 production was inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…2C ). These results are similar to those of the previous study [ 11 ] considering that the ethanol extract of U. pinnatifida roots reduces the inflammatory cytokines IL-6, TNF-α, and IL-1β secretion and has an inflammation-suppressing effect. Nevertheless, this study demonstrated that the treatment of U. pinnatifida roots with crude enzyme from S. oneidensis PKA 1008 can further improve the secretion inhibitory effect of inflammatory cytokines.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…2C ). These results are similar to those of the previous study [ 11 ] considering that the ethanol extract of U. pinnatifida roots reduces the inflammatory cytokines IL-6, TNF-α, and IL-1β secretion and has an inflammation-suppressing effect. Nevertheless, this study demonstrated that the treatment of U. pinnatifida roots with crude enzyme from S. oneidensis PKA 1008 can further improve the secretion inhibitory effect of inflammatory cytokines.…”
Section: Resultssupporting
confidence: 92%
“…Kang et al . [ 11 ] reported that the U. pinnatifida root ethanol extract treated group inhibited NO secretion by up to 34% compared to the LPS-treated control. On comparison, our results revealed that the UPT enzymatic extract was more effective in inhibiting NO secretion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations